KEMAMPUAN KONEKSI MATEMATIS SISWA DITINJAU DARI KECEMASSAN BELAJAR PADA SISWA SMP PADA MATERI LINGKARAN - Ayu Aprilianti Dwi Fani; Kiki Nia Sania Effendi (JPMI (Jurnal Pembelajaran Matematika Inovatif), 2021)
This study aim to determine how the ability of mathematical connections in terms of the anxiety of junior high school students learning in completing questionnaires and questions related to circle material. Circle material is one of the junior high school mathematics teaching materials contained in the basic competencies of class VIII. The subjects in this study were students of class VIII J in one of Karawang regencies. School year 2019/2020. This research uses a qualitative approach with descriptive methods. The instrument of learning anxiety questionnaire based on the grid and the test items urain students' mathematical connection ability is written based on the item grid grid according to the indicators, basic competencies, and material. Data collection techniques used in this study are to provide learning anxiety questionnaires and tests a description of students' mathematical connection abilities of 4 questions. The results of this study were 3 students with high learning anxiety, 24 students with moderate learning anxiety, and 3 students with low learning anxiety. The conclusion that students with low learning anxiety can achieve each indicator of mathematical connection ability, while students with low and moderate learning anxiety cannot achieve each indicator of mathematical connection ability.